2018
DOI: 10.1002/admt.201800203
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Thermally Stable Optical Polarizers Based on Highly Aligned Carbon Nanotube Sheets for the Visible Spectral Range

Abstract: Development of new types of optical components applicable to flexible and stretched substrates is essential for designing innovative display platforms for wearable and outdoor applications. Here, a novel polarizer based on highly aligned macroscopic carbon nanotube (CNT) sheets with flexibility, thermal stability, high polarization efficiency, and high transmittance is introduced. Since the conductive multiwalled CNTs are essentially held together by van der Waals forces, wire‐grid‐type polarizers of well‐alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Dielectrophoresis, the force that the particle is subjected to in an AC electric field, allows the assembly of particle chains with different patterns by changing the field intensity, frequency, and electrodes structure, etc., which has been demonstrated in our previous report . Herein, as a potential application, we show the application of gels containing oriented particle chains in grating, which is an exciting development and brings many leads to the field of photonic crystals. …”
Section: Introductionmentioning
confidence: 55%
“…Dielectrophoresis, the force that the particle is subjected to in an AC electric field, allows the assembly of particle chains with different patterns by changing the field intensity, frequency, and electrodes structure, etc., which has been demonstrated in our previous report . Herein, as a potential application, we show the application of gels containing oriented particle chains in grating, which is an exciting development and brings many leads to the field of photonic crystals. …”
Section: Introductionmentioning
confidence: 55%
“…Extraordinary polarization capability was reported by Kaili Jiang et al [18] that aligned CNT yarns reached 92% degree of polarization (DOP) in the ultraviolet region at 325 nm wavelength. In the visible spectral range, the CNT film average transmittance of 60% and the DOP of 70% have been achieved simultaneously by moonyoung Jun et al [19]. Moreover, the extinction ratio(ER) of the CNT sheet polarizer reached ∼37 dB in the broad terahertz range from 0.1to2.0 THz, which is regarded as a more prospective wave band [5].…”
Section: Introductionmentioning
confidence: 95%
“…For the ultraviolet region, even the wavelengths in the regions of tens of nanometers, Kaili Jiang et al [ 14 ] reported the remarkable polarimetric capacity of the CNT polarizer, and a 92% degree of polarization (DOP) was obtained at 325 nm wavelength. Moonyoung Jun et al [ 20 ] prepared a CNT polarizer with a transmittance of 60% and a DOP of 70% in the visible spectral range. More significantly, in a broader terahertz range from 0.1~2.0 THz, the extinction ratio of the CNT polarizer was reported to reach nearly 37 dB [ 21 ].…”
Section: Introductionmentioning
confidence: 99%